2017
DOI: 10.1007/s10528-017-9794-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers for Non-functioning Invasive Pituitary Adenomas were Identified by Using Analysis of microRNAs Expression Profile

Abstract: The microRNAs (miRNAs) are involved in multiple pathological processes among various types of tumors. However, the functions of miRNAs in benign brain tumors are largely unexplored. In order to explore the pathogenesis of the invasiveness in non-functional pituitary adenoma (NFPA), the miRNAs expression profile was analyzed between invasive and non-invasive non-functional pituitary adenoma by miRNAs microarray. Six most significant differentially expressed miRNAs were identified including four upregulated miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Of them, miR-493-5p and miR-124-3p were significantly downregulated while miR-181b-5p was upregulated. Wu et al [41] also reported four upregulated (miRNAs hsa-miR-181b-5p, hsa-miR-181d, hsa-miR-191-3p, and hsa-miR-598) and two downregulated miRNAs (hsa-miR-3676-5p and hsa-miR-383) in NFPA samples. By performing Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, they demonstrate that these differentially-expressed miRNAs are related to a series of biological processes and several signaling pathways [41].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Of them, miR-493-5p and miR-124-3p were significantly downregulated while miR-181b-5p was upregulated. Wu et al [41] also reported four upregulated (miRNAs hsa-miR-181b-5p, hsa-miR-181d, hsa-miR-191-3p, and hsa-miR-598) and two downregulated miRNAs (hsa-miR-3676-5p and hsa-miR-383) in NFPA samples. By performing Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, they demonstrate that these differentially-expressed miRNAs are related to a series of biological processes and several signaling pathways [41].…”
Section: Discussionmentioning
confidence: 94%
“…Wu et al [41] also reported four upregulated (miRNAs hsa-miR-181b-5p, hsa-miR-181d, hsa-miR-191-3p, and hsa-miR-598) and two downregulated miRNAs (hsa-miR-3676-5p and hsa-miR-383) in NFPA samples. By performing Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, they demonstrate that these differentially-expressed miRNAs are related to a series of biological processes and several signaling pathways [41]. Thus, these miRNAs may play a role in modulating the processes in NFPA progression, particularly miR-181b-5p, which needs further functional and mechanistic validations.…”
Section: Discussionmentioning
confidence: 94%
“…Among these predicted potential target miRNAs, hsa-miR-24-2-59 is reported to be upregulated during hematopoietic cell terminal differentiation, suppressing MYC expression [29]. Hsa-miR-181b-5p may play a prominent role in pituitary adenoma as an effective biomarker and therapeutic target [30]. However, there are some limitations to this study, such as a small sample size and the in vitro research being conducted only on HL-60 cells.…”
Section: Discussionmentioning
confidence: 95%
“…miRNAs are small non-coding RNAs that post-transcriptionally modulate gene expression, and whose expression is altered in several human neoplasia. For example, relevant for the topic of this review, a different miRNA expression pattern was observed in NFPAs and normal pituitary (136) with a significant influence on stem cell-related pathways, such as NOTCH (137). The field of miRNA is rapidly evolving and its application to different PASC populations might provide important novel information concerning the pathogenic mechanisms activated in these cells to originate PAs.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 97%